1992
DOI: 10.1093/cvr/26.6.631
|View full text |Cite
|
Sign up to set email alerts
|

Afterload dependent prolongation of left ventricular relaxation: importance of asynchrony

Abstract: (1) left ventricular asynchrony may increase during an acute augmentation of left ventricular afterload; (2) this increased left ventricular asynchrony possibly contributes to the afterload dependent prolongation of left ventricular isovolumetric relaxation rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…Finally, increased afterload appears to play an important role. Previous animal studies showed that an acute increase in LV afterload leads to increased dyssynchrony which was linearly correlated with (23). In the present study, a significant correlation was present between the decrease in LV ESP and the shortening in diastolic time delay after medical therapy for congestive heart failure, raising the possibility that increased afterload may have a detrimental effect on LV relaxation, in part through increased diastolic dyssynchrony.…”
Section: Hemodynamic and Echocardiographic Measurements In Shf Patiensupporting
confidence: 65%
“…Finally, increased afterload appears to play an important role. Previous animal studies showed that an acute increase in LV afterload leads to increased dyssynchrony which was linearly correlated with (23). In the present study, a significant correlation was present between the decrease in LV ESP and the shortening in diastolic time delay after medical therapy for congestive heart failure, raising the possibility that increased afterload may have a detrimental effect on LV relaxation, in part through increased diastolic dyssynchrony.…”
Section: Hemodynamic and Echocardiographic Measurements In Shf Patiensupporting
confidence: 65%
“…Multiple animal studies have demonstrated the deleterious effect of mid-to-late systolic load on LV relaxation [22, 2630]. Hori et al used a canine model to impose increased afterload by either (a) clamping the ascending aorta to induce early systolic load, (b) clamping the descending aorta to induce mid-to-late systolic load, and (c) intermittently clamping the ascending aorta in late systole.…”
Section: Effect Of Mid-to-late Systolic Load On LV Diastolic Dysfunctionmentioning
confidence: 99%
“…[19][20][21] Of these factors, increased afterload was not predominant in the present study because blood pressure was similar in the 3 groups both at rest and after DOB stress. Although no data such as negative dP/dt was available in the present study, elastic recoil did not seem to be dominant because end-systolic volume of the left ventricle was similar in the 3 groups both at rest and after DOB stress.…”
Section: Discussionmentioning
confidence: 62%
“…13,16 Pharmacological stress intervention, such as with dobutamine (DOB), is useful for detecting regional and global myocardial dysfunction in conjunction with echocardiography, and might be a more readily standardized method than exercise testing. 17,18 Furthermore, radionuclide ventriculography (RVG) might be superior to echocardiography for the assessment of asynchronous relaxation, which is an important factor affecting early diastolic filling of the left ventricle [19][20][21] and is thought to be magnified after DOB stress.Thus, we have proposed DOB stress RVG as an alternative to exercise testing, and have assessed its clinical usefulness for evaluating left ventricular performance in patients with KD. We have also analyzed risk factors that have an effect on the later myocardial dysfunction in patients who show varying degrees of coronary arterial lesions.…”
mentioning
confidence: 99%